Innovation in Public Policy Administration: The Use of In-formation Technology to Enhance Transparency and Ac-countability - Natsir Mallawi; Nurasia Natsir (International Journal of Law and Society, 2025)
Information technology (IT) has emerged as a critical component of public administration, offering significant potential to enhance transparency and accountability in governance. This comprehensive qualitative case study research examined how information technology implementation influences transparency and accountability mechanisms in public policy administration, while identifying critical challenges and success factors. The research employed embedded multi-case study methodology, collecting data through 118 semi-structured interviews with government officials (n=45), citizen-users (n=38), IT professionals (n=15), civil society representatives (n=12), and academic researchers (n=8), complemented by document analysis and direct observation (280 hours) across four case sites representing diverse governance contexts. Key findings demonstrate that information technology implementation significantly enhances government transparency through multiple mechanisms: public information portals increased citizen information access from 25-30% to 78-82%, mobile applications extended service accessibility from 15-20% to 42-55% in rural areas, and social media platforms reached 60-70% of citizens with policy information. Similarly, IT implementation strengthened accountability through online complaint systems that reduced government response times from 28-45 days to 5-12 days (60-75% improvement), automated audit systems that detected 35-55% more compliance violations, and real-time monitoring systems that reduced audit completion time by 40-50%.  The findings have implications for government practitioners seeking evidence-based guidance for IT implementation, policymakers developing governance policies leveraging technology, and academic researchers studying digital governance and public administration innovation.